Plan of the town and harbour of St. Iohn's in Newfoundland. - Debbieg, Hugh, 1731-1810 .
Digitization note: Due to its large size, this item was scanned in sections, stitched together, and edited.; Finished, detailed, topographical map of the land around St. John's harbor with an overlay for proposed fort pasted to it.; See Debbieg to Gage, Sept. 28, 1765 and finished plan of the proposed fort (Brun 50).